2020
DOI: 10.3390/jcm9082351
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Association between Air Pollution and Daily Mortality in the Capital of the Green Lungs of Poland–Population-Based Study with 2,953,000 Person-Years of Follow-Up

Abstract: (1) Introduction: air pollution is considered to be one of the main risk factors for public health. According to the European Environment Agency (EEA), air pollution contributes to the premature deaths of approximately 500,000 citizens of the European Union (EU), including almost 5000 inhabitants of Poland every year. (2) Purpose: to assess the gender differences in the impact of air pollution on the mortality in the population of the city of Bialystok—the capital of the Green Lungs of Poland. (3) Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 38 publications
(41 reference statements)
1
20
0
Order By: Relevance
“…Literature has reported that females are more likely to die due to CVDs than primarily from air pollution compared to males. This was confirmed from a study conducted in Poland where it was found that the effect of SO 2 inhalation was more pronounced in males [31,32]. As a result, the inhalation of this pollutant could cause pulmonary inflammation, resulting in thrombosis, endothelial dysfunction, imbalance of the autonomic nervous system, increased arterial pressure, and ultimately death [32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 53%
“…Literature has reported that females are more likely to die due to CVDs than primarily from air pollution compared to males. This was confirmed from a study conducted in Poland where it was found that the effect of SO 2 inhalation was more pronounced in males [31,32]. As a result, the inhalation of this pollutant could cause pulmonary inflammation, resulting in thrombosis, endothelial dysfunction, imbalance of the autonomic nervous system, increased arterial pressure, and ultimately death [32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 53%
“…CVD is still the leading cause of death and disability in the European population [ 26 ], as well as in Poland [ 27 , 28 , 29 ]. It is often silent and may occur suddenly, underscoring the importance of prevention.…”
Section: Discussionmentioning
confidence: 99%
“…In nearby Białystok it was shown that an increase in sulfur dioxide (SO 2 ) concentration by 1 µg/m 3 was related to an increase in the number of daily deaths (RR 1.07; 95% confidence interval (CI) 1.02–1.12). Interestingly, results for PM 2.5 and PM 10 were not significant [ 45 ], even though the change in PM 2.5 concentration was shown to have the greatest strength of association with daily mortality rates [ 16 , 17 ]. However, a rise of PM 2.5 concentration by 10 µg/m 3 was found to be a risk factor for increased cardiovascular deaths (RR 1.07; 95% CI 1.02–1.12) [ 45 ].…”
Section: General and Respiratory Disease Hospitalization And Mortality Ratesmentioning
confidence: 99%
“…Interestingly, results for PM 2.5 and PM 10 were not significant [ 45 ], even though the change in PM 2.5 concentration was shown to have the greatest strength of association with daily mortality rates [ 16 , 17 ]. However, a rise of PM 2.5 concentration by 10 µg/m 3 was found to be a risk factor for increased cardiovascular deaths (RR 1.07; 95% CI 1.02–1.12) [ 45 ].…”
Section: General and Respiratory Disease Hospitalization And Mortality Ratesmentioning
confidence: 99%